NK cell subsets and interactions with dendritic cells - Münz, Christian (Henry Stewart Talks, 2010)
Circulation and homeostasis of NK cells, NK cells in secondary lymphoid organs, Subsets of human peripheral blood NK cells, FcR and activation markers, Inhibitory/ Activating NK receptors, Homing markers expressed on NK cells, NK cells differentiation, Co localization of NK cells and DCs, Pathway of transmission of information by DCs, IFN-gamma production by NK cells, Pathogen pattern that lead to DC maturation, IL-12- the dominant cytokine for NK cell activation, The immunological synapse, MHC class I up-regulation protects mature DCs, Activating and inhibitory signals in the synapse, Functional relevance of NK cell activation, Function of NK cells in graft vs. host disease, NK cells and the response to Epstein Barr virus, IFN-gamma production by subsets of NK cells, Non cytotoxic functions of NK cells, Cross talk of innate lymphocytes